2010
DOI: 10.1002/prca.200900073
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of redox proteins and chaperones in HbEβ‐thalassemia erythrocyte proteome

Abstract: We have observed interesting changes in the proteomic levels of redox regulators and chaperons in the thalassemic hemolysates and have observed strong correlation or association of the extent of such proteomic changes with HbE levels. This could be important in understanding the role of HbE in disease progression and pathophysiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 35 publications
5
61
0
Order By: Relevance
“…We observed that antioxidant proteins, chaperone proteins, proteins involving in iron metabolism, hemoglobin subunit d, cathepsin S (an inflammatory marker), and erythroid proteins were consistently increased in quantity in HbE/ b-thalassemic patients across all 3 pooled samples (Table 2), and this was also observed in 6 individual samples (Table 4). Taken together, the observed alterations in protein content in the thalassemic EVs are consistent with the known increase in oxidative burden due to peripheral hemolysis reported in previous studies, 13,22,24 and this study has substantially extended the number of known proteins with an altered concentration in HbE/ b-thalassemic patients' EVs.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We observed that antioxidant proteins, chaperone proteins, proteins involving in iron metabolism, hemoglobin subunit d, cathepsin S (an inflammatory marker), and erythroid proteins were consistently increased in quantity in HbE/ b-thalassemic patients across all 3 pooled samples (Table 2), and this was also observed in 6 individual samples (Table 4). Taken together, the observed alterations in protein content in the thalassemic EVs are consistent with the known increase in oxidative burden due to peripheral hemolysis reported in previous studies, 13,22,24 and this study has substantially extended the number of known proteins with an altered concentration in HbE/ b-thalassemic patients' EVs.…”
Section: Discussionsupporting
confidence: 91%
“…These data 0.14 strengthen the hypothesis that the circulating plasma EVs are derived in part from erythrocyte lysis. 22 Finally, an increase in the quantity of cathepsin S, a potent elastolytic protease, was detected in thalassemic EVs, which may originate from activated myeloid cells. 23 Only 2 proteins, hemopexin and haptoglobin, were consistently and significantly reduced (12.5-to 25-fold and 7.1-to 20-fold reduction, respectively) in the patient compared with control EV samples across the 3 experiments (Table 3).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Severe patients, compared with mild patients, had an increase in markers of RBC oxidative stress based on ineffective erythropoiesis, lower RBC counts, PS exposure, greater serum EPO and plasma malondialdehyde (MDA), and RBC SOD. Other laboratories have shown not only an increase in RBC redox enzymes, such as PRDX2, catalase, thioredoxin, and SOD, but also an increase in the alpha globin chaperone, alpha hemoglobinstabilizing protein, negatively correlated with MCH and HbF (18,102,189).…”
Section: Fig 2 Hbe Acts As a Bmentioning
confidence: 96%